Citizen Welles : A Biography of Orson Welles - Brady, Frank, 1934- (Book collections on Project MUSE., 2023)
In Citizen Welles: A Biography of Orson Welles, author Frank Brady presents a comprehensive and complete picture of the artist and auteur. Painstakingly researched, Brady delves into Welles's creative achievements, from his critically acclaimed film Citizen Kane and controversial radio broadcast "The War of the Worlds" (1938) to his starring turn on Broadway in Shaw's Heartbreak House (for which he made the cover of Time). Brady also explores other notable films, including The Magnificent Ambersons (1942), Touch of Evil (1958), and Chimes at Midnight (1965). This all-encompassing work also details the personal side of Welles's life, including his romances with Rita Hayworth and Dolores Del Rio and the confounding tragedy of his final years. Presented is a captivating and compelling encapsulation of the revered and respected artist.